Crowdfunding in Kenya: Factors for Successful Campaign: The Case of Kickstarter Crowdfunding Platform - Wachira, Esther Wanjiru; Wachira, Virginia Kirigo (Public Finance Quarterly, 2023)
The study aimed at investigating the factors that lead to successful crowdfunding campaigns in Kenya. The success factors of reward-based crowdfunded campaigns vary in different countries due to differences in cultures, legal requirements, social interactions, political and business environments. With very minimal research on crowdfunding funding in Kenya, the study therefore, aimed at analyzing reward-based crowdfunding in Kenya using Kickstarter data, and identifying the crucial factors necessary to run a successful campaign. To achieve this objective, the study used a multiple regression and Pearson correlations. The study found a statistically significant regression equation hence the regression model was considered a good fit. The study using the Pearson correlations analysis found a very strong and positive statistical correlation between updates, amount pledged, backers, and successful projects, moderate but positive statistical correlation between comments, new backers, returning backers, and successful projects. However, there was a negative but insignificant correlation between the goal, funding period, and successful projects. The novelty will be of great benefit to project funders who want to run successful projects in Kenya. This is because the concept of crowdfunding is still new in Kenya and has not been widely publicized, accepted, or researched. The results of this study will guide potential founders on the do’s and don’ts of running a successful campaign. Finally, the study recommends further research on the success factors of other crowdfunding models in Kenya as the study solely focused on the reward-based model.